Nilai Pendidikan Islam dan Relevansinya dengan SDGs dalam Syair Sayid Idrus bin Salim Al-Jufri: Analisis Semiotika Roland Barthes: Nilai-Nilai Pendidikan Islam dan Pembangunan Berkelanjutan: Studi Semiotik Puisi “al-ʿIlm” Karya Sayid Idrus bin Salim Al-Jufri Melalui Kerangka Teori Roland Barthes - Nida Fauziyah Fitriani; Minatur Rokhim; Nur Hasaniyah; Fikri Aulia (Language Development Center, 2025)
Background: Islamic education integrates knowledge, faith, and morality to foster holistic character building and sustainable social development, while addressing the existing research gap concerning the limited scholarly attention toward classical Islamic poetry in the context of the Sustainable Development Goals (SDGs). Objective: This study examines the values of Islamic education and their relevance to the SDGs as reflected in the poetry of Sayid Idrus bin Salim Al-Jufri through Roland Barthes’ semiotic framework, analyzing five selected stanzas (n = 5) from his poem al-‘Ilm. Method: Using a descriptive qualitative-analytical design, this research applies Barthes’ three levels of semiotic analysis denotative, connotative, and mythological to interpret educational, moral, and spiritual meanings. The five stanzas were selected through purposive sampling based on their representation of Al-Jufri’s educational and ethical values. The analysis was supported by semiotic tables, literature documentation, and validation through theoretical and source triangulation to ensure analytical reliability. Results: The findings reveal core Islamic educational values including the pursuit of knowledge, moral integrity, social responsibility, and devotion to God. These values align with SDG 4 (Quality Education), SDG 16 (Peace, Justice, and Strong Institutions), and SDG 17 (Partnerships for the Goals). The study also highlights the theoretical significance of integrating Barthesian semiotics with Islamic literary tradition, and its practical contribution to strengthening value-based educational discourse. Conclusion: The poem al-‘Ilm serves as an effective semiotic medium for value-based education, contributing to sustainable human development and offering insights for future research on sustainability-oriented Islamic education in the modern era.